Transforaminal endoscopic lumbar discectomy with targeted puncture and foraminotomy for very highly migrated disc herniation: A technique note with case series - Jun-Jie Shen; Xin Wang; Bin Cai; Yuan-Yuan Chen; Guo-Wang Zhang; Jian-Guang Xu; Xiao-Feng Lian (Heliyon, 2022)
Background: Transforaminal endoscopic lumbar discectomy (TELD) has been widely used for lumbar disc herniation. However, in some challenging cases such as very highly migrated disc herniation (VHMDH), traditional TELD is difficult to access the pathology. Methods: From January 2016 to December 2019, 63 patients with single-level VHMDH underwent TELD using targeted puncture and foraminotomy techniques were included. All patients were followed up for 26.5 months on average (range, 24–48 months). Operative time, length of hospital stay, visual analog scale (VAS) score, Oswestry Disability Index (ODI), modified MacNab criteria and surgical complications were evaluated. Results: The operative time was 40–120 min (56.8 on average). The length of hospitalization was 2.5 days (range, 2–4 d). VAS score decreased significantly from 5.5 ± 1.3 preoperatively to 1.9 ± 1.30 (p < 0.001) 1 day postoperatively, and to 0.9 ± 0.8 (p < 0.001) at the final follow-up. ODI score improved significantly from 23.5 ± 3.2 preoperatively to 13.4 ± 3.0 (p < 0.001) 1 day postoperatively; and 3.1 ± 1.2 (p < 0.001) at the final follow-up. According to the modified MacNab criteria, 40 patients (63.5%) showed excellent results, 20 patients (31.7%) were rated as good, 2 patients (3.2%) were rated as fine, and 1 patient (1.6%) was rated as bad at the final follow-up. No residual fragments, nerve root or cauda equina injury was shown in this series. One recurrent case was resolved by open surgery. Conclusions: With modified targeted puncture and foraminotomy techniques, VHMDH can be accessed safely and effectively, and satisfactory clinical outcomes can be obtained for these patients.